Encyclopedia of the United States in the nineteenth century - Finkelman, Paul, 1949- (New York : Charles Scribner's Sons, 2001)
'The 19th century was arguably the most important in the nation's history, making the publication of this first-rate encyclopedia a significant event. Students using this 600-entry work, which is conveniently keyed to the National Standards for United States History, will find the entries easy to follow and enjoyable to read. It is an essential purchase for all public and academic libraries.'--'Outstanding Reference Sources,' American Libraries, May 2002.
v. 1. Abolition and antislavery-government -- v. 2. Grand tour-presidency -- v. 3. Printing technology-zoos
Maps on lining papers
Includes bibliographical references and index
Keywords: United States -- Civilization -- 19th century -- Encyclopedias